Prevalence and tools for assessment of postpartum depression : a systematic review and meta-analysis - Salleh, Mohd Noor Izzad Mohd (2023)
Background: The World Health Organization (WHO) projected depression to be the leading cause of disability by 2030. Previously under-reported and often disregarded as normal physiology after childbirth, the prevalence of postpartum depression has been steadily increasing and recognized as a public health concern. This review aimed to estimate the updated global prevalence of postpartum depression and identify the screening tools used to assess this condition. Methodology: MEDLINE, Google Scholars, PUBMED, SCOPUS and ScienceDirect databases were searched for articles from year 2010–2020 that reported the prevalence of postpartum depression. A total of 172 studies were included in this review. Result: The overall global pooled prevalence of postpartum depression was increasing in recent years from 2010-2020 at 20.60% (95% CI: 19.31%, 21.88%); higher in developing countries (23.29%, 95%CI: 21.45%, 25.12%) compared to developed countries (11.35%, 95% CI: 9.88%, 12.82%). The overall prevalence was highest at 25.35% (95% CI:18.63%, 32.06%) when screened up to 12 months postpartum in developing countries, and at 18.53% (95%CI: 12.91%, 24.14%) when screened within four weeks postpartum in developed countries. A high prevalence was reported among military personnel (83.0%), mothers with neonatal complications (78.4%), mother with antenatal complications (45.88%), victims of domestic violence (27.9%), and immigrants (22.4%). Edinburgh Postnatal Depression Scale (EPDS) alone was utilized to detect this condition in 83.1% of the studies in which 130 out of 142 of these studies used a cut-off points value of ten or higher. Conclusion: The increasing prevalence of postpartum depression is a significant concern globally showing that it affects the mother’s health and has dire impacts on the children’s health. All mothers should be screened for postpartum depression at an appropriate time interval. Issues about sexual and reproductive health, women’s rights, and violence must be incorporated into the well-established premarital course to reduce the risk of getting this condition incited by domestic violence.